Diagnostic accuracy of OGUS, Southend halo score and halo count in giant cell arteritis - Conticini, Edoardo; Falsetti, Paolo; Al Khayyat, Suhel Gabriele; Grazzini, Silvia; Baldi, Caterina; Bellisai, Francesca; Gentileschi, Stefano; Bardelli, Marco; Fabiani, Claudia; Cantarini, Luca; Dasgupta, Bhaskar; Frediani, Bruno (Frontiers in Medicine, 2024)
Objectives Ultrasound has a paramount role in the diagnostic assessment of giant cell arteritis (GCA); Southend halo score (HS), halo count (HC) and OMERACT GCA Ultrasonography Score (OGUS) are the first quantitative scores proposed in this setting. Aim of this study was therefore to assess diagnostic accuracy of these scores in a real-life scenario, as well as to evaluate their optimal cut-off, also with respect to disease extent, sex and age. Methods We retrospectively collected clinical, serological and US findings of all patients referred for the first time to our vasculitis clinic in the suspicion of GCA. Results A total of 79 patients were included and a definite diagnosis of GCA was made in 43. For OGUS, the ROC curve showed an optimal cut point of 0.81 (sensitivity 79,07%, specificity 97,22%). For HC and HS, the optimal cut-off values were respectively >1.5 (sensitivity 76,7%, specificity 97,2%) and >14,5 (sensitivity 74,4%, specificity 97,2%). No relevant differences were assessed when patients were stratified according to disease extent, age and sex. Compression sign (CS) was positive in 34/38 patients with cranial GCA and negative in all controls and LV GCA. Conclusions All three scores display a good sensitivity and an excellent specificity, although at cut-off slightly different than proposed. In particular, for OGUS, a threshold of 0,81 could be employed for diagnostic purposes, although it was developed solely for monitoring. Due to its high sensitivity and specificity, CS should be always assessed in all patients referred with a suspicion of cranial GCA.